Exploitation of Inland-Breeding Antarctic Petrels by South Polar Skuas - Brooke, Michael de L; Keith, Dave; Røv, Nils (Oecologia, 1999)
During the austral summer of 1996/1997 we studied south polar skuas at Svarthamaren, Dronning Maud Land, Antarctica, where the world's largest known colony of Antarctic petrels is found. Our censuses suggested approximately 250 full-grown skuas and 140,000 breeding pairs of petrels were present. During their breeding season, skuas did not visit the open sea at least 200 km from the site; they relied entirely on prey caught and scavenged from the petrel colony. Because the site is so isolated, we asked whether the prey (petrels) had swamped the predators (skuas), or whether there was evidence that predator numbers were limited by the size of the prey population. Particularly at the end of the petrel incubation period, we found a close correspondence between the energy required by adult skuas and their chicks, ascertained from time budget studies, and the rate at which petrel eggs disappeared from the colony. This suggests that, in this closed system, the predator population was limited by the prey population, and that predator swamping was not an advantage that petrels gained by nesting in this remote location.
Publisher: Springer
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

The influence of ornithogenic products on the nutrient status of soils surrounding nests on nunataks in Dronning Maud Land, Antarctica - Cocks, Martin P; Harris, Jean M; Steele, William K; Balfour, Dave A (Polar Research, 1999)
Keywords: Dronning Maud Land; fugler; nunataker; næringsstoff; ornitologi; petreller

Combined use of field observations and SAR interferometry to study ice dynamics and mass balance in Dronning Maud Land, Antarctica - Dietrich, Reinhard; Metzig, Robert; Korth, Wilfried; Perlt, James (Polar Research, 1999)
In the region of the Schirmacheroase (71 °S, 12°E) various geodetic and glaciological research activities have been carried out in the last decade. Several times three geodetic-glaciological traverses were undertaken to study ice velocity, accumulation and ablation, and ice surface height changes. Repeated ground surveys show a significant decrease in surface heights by about 15 cm/y for a large blue-ice area. This paper presents the first interferometrically derived ice velocity field of the inland ice close to the Schirmacheroase. The interferometric analysis of the synthetic aperture radar (SAR) data is performed in combination with ground-based information. Since only ERS-1&2 tandem mission image couples are available for this region a digital elevation model (DEM) is used to remove the effect of topography. Ice velocities up to 100 m/y are proved interferometrically for this part of the inland ice.
Keywords: Dronning Maud Land; geodesi; glasiologi; innlandsis

Variability in snow layering and snow chemistry in the vicinity of two drill sites in western Dronning Maud Land, Antarctica - Hansson, Margareta; Holmlund, Per; Karlöf, Lars; Stenberg, Malin (Annals of Glaciology, 1999)
As part of the pre-site survey in Dronning Maud Land for the European Project for Ice Goring in Antarctica (EPICA), the spatial variability of snow-layer thickness and snow chemistry was studied at two geographically different ice-core drill sites. The study aimed to quantify error bars on accumulation rates derived from firn and ice cores. One site is located on the polar plateau at Amundsenisen (76° S, 8° W) and the other in the coastal area at Maudheimvidda (73° S, 13° W). Medium-deep ice cores (100 m) and shallow firn cores (10-20 m) were drilled and snow pits (0.5-2 5 m) were dug at each site. At Amundsenisen a large (16 m x 6 m x 2.5 m deep) snow pit was dug. Snow structure in this large snow pit was mapped using optical surveying equipment, and photographically documented. Samples for analysis of nine ions and oxygen isotopes were collected along one depth profile. Density and in situ electrical conductivity measurements were made along three depth profiles! Snow-layer variability was studied in two different areas and at two different scales. At a regional scale, measured by snow-radar soundings, the variability was 8% on the polar plateau and 45% in the coastal area. The variability at a micro-scale in the large snow pit was 9%. The results indicate that ice cores from the polar plateau are more representative for a larger area than ice cores drilled in the coastal area There is no doubt that there are significant error bars on high-resolution accumulation data received from firn and ice cores, especially from the coastal area, but averaging over tens of years reduces the error in accumulation estimates.
Edition: 2017/09/14 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; fysisk geografi; geokjemi; glasiologi; iskjerner; paleoklimatologi

Accumulation and proxy-temperature variability in Dronning Maud Land, Antarctica, determined from shallow firn cores - Isaksson, Elisabeth; van den Broeke, Michiel R; Winther, Jan-Gunnar; Karlöf, Lars; Francis Pinglot, Jean; Gundestrup, Niels (Annals of Glaciology, 1999)
During 1996-97 a European Project for Ice Goring in Antarctica (EPIGA) pre-site surveying traverse worked in the area between 70° S, 5° E and 75° S, 15° E in Dronning Maud Land. We present data obtained from 10 and 20 m deep firn cores drilled between the coast and 600 km inland (to 3450 m a.s.l.). The cores were analyzed for electrical conductivity measurements and total β activity to obtain accumulation data between known time horizons. In addition, some of the cores were analyzed for oxygen isotopes. Annual accumulation varies from 271 mm we. at Fimbulisen to 24 mm we at 2840 m a.s.l. Accumulation at core sites 2400-3000 m a.s.l. has increased by 16-48% since 1965 compared to the 1955-65 period. However, the core sites above 3250 m a.s.l. and one core location on the ice shelf show a decrease during the same period. Furthermore, no change can be detected at the most inland site for the period 1815-1996. In all the cores the last few years seem to have been some of the warmest in these records.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi

EPICA Dronning Maud Land pre-site survey - Karlöf, Lars; Gjerde, Knut; Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; geodesi; innlandsis; topografi

Meltwater production in Antarctic blue-ice areas: sensitivity to changes in atmospheric forcing - Liston, Glen E.; Bruland, Oddbjørn; Winther, Jan-Gunnar; Elvehøy, Hallgeir; Sand, Knut (Polar Research, 1999)
In the near coastal regions of Dronning Maud Land, Antarctica, below-surface ice-melt in blue-ice areas has been observed. The low scattering coefficients of the large-grained blue-ice allow penetration of solar radiation, thus providing an energy source below the ice surface. The sub-surface meltwater is significant enough to show up on remote-sensing imagery in the form of ice-covered lakes. Adjacent snow-accumulation areas have much higher scattering coefficients and consequently limit solar radiation penetration in these regions. These snow and ice surfaces are generally below freezing, and little surface melting occurs. To assess the response of these melt features to changes in atmospheric forcings such as cloudiness, air temperature, and snow accumulation, a physically-based model of the coupled atmosphere, radiation, snow, and blue-ice system has been developed. The model consists of a heat transfer equation with a spectrally-dependent solar-radiation source term. The penetration of radiation into the snow and blue-ice depends on the surface albedo, and the snow and blue-ice grain size and density. Model simulations show that ice melt occurring in this area is sensitive to potential variations in atmospheric forcing. Under certain conditions more traditional surface melting occurs and, under other conditions, the existing melt processes can be shut down completely. In light of the sensitivity of this system to variations in atmospheric forcing, and the ability to view melt-related features using remote sensing, a tool exists to efficiently monitor variations in Antarctic coastal climate.
Keywords: Dronning Maud Land; NARE 1996/97; blåis; glasiologi; innlandsis; isshelf; smelting

Studies of seabirds at Svarthamaren - Tveraa, Torkild; Andreassen, Cecilie; Christensen, Guttorm N (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; fugler; ornitologi; petreller

Distribution and Abundance of the Antarctic Petrel - van Franeker, J. A.; Gavrilo, M.; Mehlum, Fridtjof; Veit, R. R.; Woehler, E. J. (Waterbirds: The International Journal of Waterbird Biology, 1999)
Published and unpublished information on the distribution and abundance of the Antarctic Petrel (Thalassoica antarctica) is reviewed. Currently 35 colonies with approximately half a million breeding pairs are known. All but one of these known colonies are situated in East Antarctica. However, an estimate derived from at sea studies in three of four apparent centers of oceanic occurrence suggests a population as high as four to seven million breeding pairs (10 to 20 million individuals). In spite of the tentative nature of such an estimate, the difference with the colony-derived figure strongly suggests the existence of large, currently undiscovered colonies, particularly in western Antarctica and Victoria Land, where a complete mismatch exists between bird observations at sea and known colonies. In eastern Antarctica, in addition to undiscovered colonies, some known ones could be considerably larger than currently documented.
Publisher: Waterbird Society
Keywords: Antarktis; Dronning Maud Land; fugler; ornitologi; petreller; zoologi

Sixty year 10Be record from Greenland and Antarctica - Aldahan, A.; Possnert, G.; Johnsen, S. J.; Clausen, H. B.; Isaksson, Elisabeth; Karlen, W.; Hansson, M. (Proceedings of the Indian Academy of Sciences - Earth and Planetary Sciences, 1998)
We report in this study the distribution of 10Be in the top 40 m of the Renland ice core (East Greenland) and in a 30 m long core from DML (Dronning Maud Land, Antarctica) for the period 1931–1988. The two sites show differences in10Be content, the Antarctica site showing smaller variance and a lower average 10Be annual flux. Similarly, the average accumulation rate (cm water equivalent year−1) is higher in the Renland relative to DML. The variability in accumulation (precipitation) rates seems to explain part of the difference in10Be flux between the two polar sites. Cyclic fluctuations of 10Be flux correlate with the 11-year sunspot number and cosmic ray intensity than with the aa index (perturbation of the geomagnetic activity by the solar wind). Our data corroborate 10Be cyclic fluctuation pattern from the Dye 3 ice core and confirm a promising potential for correlation of global and local events.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi; meteorologi; polarområdene

Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Diet and prey consumption of Antarctic petrels Thalassoica antarctica at Svarthamaren, Dronning Maud Land, and at sea outside the colony - Lorentsen, Svein-Håkon; Klages, Norbert; Røv, Nils (Polar Biology, 1998)
The diet of the Antarctic petrel Thalassoica antarctica was studied during two seasons at Svarthamaren, an inland colony in Dronning Maud Land, Antarctica, and in the pack ice off the coast of Svarthamaren. The most important food (wet mass) at Svarthamaren was crustaceans (67%), fish (29%) and squid (5%); however, individuals collected in the pack ice took mostly fish (87%). The prey composition and lengths of prey are comparable to what has been documented in other studies on this species. Estimates of food consumption by birds breeding at Svarthamaren (ca. 250,000 pairs) suggest that approximately 6500 tonnes of crustaceans, 2800 tonnes of fish and 435 tonnes of squid are consumed during the breeding season. The annual consumptions of these birds are estimated to be 34,100 tonnes of crustaceans, 14,700 tonnes of fish, and 2300 tonnes of squid. Satellite telemetry data indicate that Antarctic petrels from Svarthamaren may fly more than 3000 km during one foraging trip, and thus may cover a huge ocean area to obtain their prey.
Keywords: Dronning Maud Land; NARE 1991/92; NARE 1993/94; fugler; ornitologi; petreller; zoologi

Large spatial variation in accumulation rate in Jutulstraumen ice stream, Dronning Maud Land, Antarctica - Melvold, Kjetil; Hagen, Jon Ove; Pinglot, Jean Francis; Gunuestrup, Niels (Annals of Glaciology, 1998)
A mass-balance programme was initiated on Jutulstraumen ice stream, western Dronning Maud Land,Antarctica, during the austral summer 1992-93. As a part of the mass-balance programme, accumulation rate was measured along the centre line of Jutulstraumen from the shelf edge up to the plateau at about 2500 m a.s.l. Accumulation distribution obtained from seven shallow firn cores and 48 slake readings is presented. The overall net accumulation trend displays a decreasing accumulation with increasing elevation and distance to coast, but on both the mesoscale and microscale there are significant variations. This is due to complex patterns of precipitation controlled by orography and redistribution by katabatic winds. The local accumulation distribution (few km scale) was found to be dependent on downslope surface gradient (aspect north, northwest), and variations up to 100% were found over distances of less than 3 km. The large variation in accumulation is important when selecting new core sites and for interpretation of temporal and spatial variations in accumulation derived from firn cores.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; geofysikk; geografi; glasiologi; isstrøm

Regulation of food provisioning in the Antarctic petrel; the importance of parental body condition and chick body mass - Tveraa, Torkild; Sether, Bernt-Erik; Aanes, Ronny; Erikstad, Kjell Einar (Journal of Animal Ecology, 1998)
1. Two hypotheses may explain how long-lived seabirds regulate the food provisioning to their chick. The fixed level of investment hypothesis states that the parents provide food for their chick according to an intrinsic rhythm, independent of their chick's need. The flexible investment hypothesis states that the parents adjust their food provisioning both according to their chick's and their own need. 2. We tested how the Antarctic petrels adjust the food-provisioning according to their own body condition or to their chick's need. First, we selected parents in poor and good body condition. Then we gave all parents randomly a chick of different body mass, but of the same age. We then measured the chicks daily until they were fed for the first time after swapping. 3. Parents in good body condition at hatching were more likely to produce a chick that was still alive 9 days after hatching than parents in poor body condition. Chick body mass at day 9 and at the end of the guarding period was positively related to the mean body condition of the parents at hatching. 4. The meal size provided by parents in good body condition was larger than that provided by parents in poor body condition. Parents in good body condition delivered more food to small than to large chicks, whereas no such relationship was found among parents in poor body condition. 5. Our results suggest that the Antarctic petrel parents adjust the amount of food delivered to their chick according to both the chick's need and their own body condition, and that the ability to respond to the chick's need is dependent upon their own body condition.
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

Body mass and parental decisions in the Antarctic petrel Thalassoica antarctica : how long should the parents guard the chick? - Tveraa, Torkild; Sæther, Bernt-Erik; Aanes, Ronny; Erikstad, Kjell Einar (Behavioral Ecology and Sociobiology, 1998)
In Procellariiformes, the parents guard the chick after it has attained homeothermy. This strategy may reduce the probability that a small chick is taken by predators, but is costly as only one parent can forage at a time. The decision to leave the chick may therefore be a compromise between the chick's vulnerability to predators, the body condition of the parent on the nest and whether the foraging parent returns in time. We studied how the number of days that parents guarded the chick was related to the body mass of the parent at the nest and the time the foraging parent spent at sea in the Antarctic petrel Thalassoica antarctica. We also examined how the body mass of the parent on the nest and the duration of the foraging trips influenced the chicks' body condition at the end of the guarding period. When the foraging parent did not return to the nest in time to relieve its mate, the number of days the parent on the nest kept guarding the chick was positively related to its body mass on arrival in the colony. The number of days the foraging parent spent at sea was positively related to the body mass of its mate, but those that returned in time had a shorter stay at sea relative to their mate's body mass than those that did not return before their mate had left. Apparently, both the body mass of the parent at the nest and the ability of the foraging parent to adjust its stay at sea to the mate's body mass is important for the number of days the parents guard the chick and also the chick's body condition at this point. The inability to return to the nest before the mate has left may be the result of needing a minimum amount of time at sea to find food, or because some parents having low foraging success and therefore prolong their stay at sea.
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller; zoologi

Kvitkuven: Kronprinsesse Märtha Kyst (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet B6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet C7S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1997)
Pages: Blad/Sheet B7S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Geological observations in Gjelsvikfjella, Mühlig-Hogmanfjella and western Orvinfjella during NARE 96/97 - Austrheim, Håkon; Elvevold, Synnøve; Engvik, Ane K; Paulsson, Oskar (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; geologi

Geodetic measurements in Dronning Maud Land - Barstad, Bjørn; Eiken, Trond; Finnes, Randi; Øvstedal, Ola (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; geodesi; målinger

Geodetic and topographic work - Barstad, Bjørn; Eiken, Trond; Lytskjold, Bjørn (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; geodesi; topografi

Representation of Antarctic Katabatic Winds in a High-Resolution GCM and a Note on Their Climate Sensitivity - Broeke, Michiel R. van den; Wal, Roderik S. W. van de; Wild, Martin (Journal of Climate, 1997)
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Antarktis; Dronning Maud Land; glasiologi; klimatologi; meteorologi

Zooplankton in the marginal ice zone off Dronning Maud Land - population structure and trophic relationship - Falk-Petersen, Stig; Lønne, Ole Jørgen (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; alger; fytoplankton; krill; zooplankton

Shallow seismic investigations and sediment sampling in the Weddell Sea amd Dronning Maud Land - Forsberg, Carl Fredrik; Austin, W E N; Häkkinen, Väinö Ami Juhani; Andersen, Espen Sletten (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; Weddellhavet; ekspedisjoner; marin geologi; sedimenter; seismologi

Mass balance and dynamics on Jutulstraumen ice stream - Hagen, Jon Ove; Melvold, Kjetil (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isshelf; isstrøm; klimaendringer; snø

Study of velocity, mass flow and deformation in Jutulstraumen - Høydal, Øyvind Armand (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isstrøm

Mass balance and dynamics on Jutulstraumen ice stream, NARE 1996/97 - Melvold, Kjetil; Hagen, Jon Ove; Laumann, Tron; Rolstad, Cecilie (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fysisk geografi; glasiologi; isstrøm

Airborne radar soundings of ice depth, GPS measurements of ice velocity and studies of landform evolution in central Dronning Maud Land East Antarctica - Näslund, Jens Ove (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isstrøm; topografi

Distribution and food consumption of crabeater seals off Dronning Maud Land - Nordøy, Erling S; Blix, Arnoldus Schytte (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; seler; zoologi

Spatial distribution of snow in western Dronning Maud Land, East Antarctica, mapped by a ground-based snow radar - Richardson, Cecilia; Aarholt, Eldar; Hamran, Svein-Erik; Holmlund, Per; Isaksson, Elisabeth (Journal of Geophysical Research: Solid Earth, 1997)
During the austral summer 1993/1994, the spatial distribution of snow was mapped by a ground-based snow radar (800–2300 MHz) in western Dronning Maud Land, East Antarctica. Snow radar soundings were performed along continuous profiles extending from the ice shelf up to the polar plateau, a total distance of 1040 km. The high-resolution radar registrations revealed subsurface layering in the uppermost 12 m of the snowpack. The travel time record was translated into snow accumulation expressed in water equivalents, based on an empirical relationship between wave speed and firn density. A good knowledge on snow density variations with depth is essential for the variability studies. Generally, the snow layering was well developed in the coastal area and less well developed on the polar plateau. High spatial variability in snow accumulation was observed on a regional as well as on a local scale. The variability was very high in areas with large surface slopes, such as the grounding zone and around nunataks. The highest variability was recorded in the nunatak area, where the standard deviation reached 59% of the spatial average accumulation. On the smooth high-altitude plateau, variations in accumulation were less pronounced. However, here the standard deviation exceeded 22% of the average accumulation rate. Provided that the snow radar soundings are supported by dating of reference horizons along the travel route, this is a good method to obtain the accumulation rate and pattern for large areas with a high spatial resolution.
Keywords: Dronning Maud Land; fysisk geografi; geofysikk; geokjemi; glasiologi; iskjerner

Changing mass balance of the Filchner ice shelf due to climate variations - Solås, Monica Kristensen; Eggenfellner, Heinrich (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isshelf; klimaendringer

Size-Dependent Variation in Reproductive Success of a Long-Lived Seabird, the Antarctic Petrel (Thalassoica Antarctica) - Sæther, Bernt-Erik; Lorentsen, Svein-Håkon; Tveraa, Torkild; Andersen, Reidar; Pedersen, Hans Christian (The Auk, 1997)
We examined how variation in parental quality influences the reproductive success of a long-lived seabird, the Antarctic Petrel (Thalassoica antarctica). In particular, we focused on how quality of parents can interact with and influence the effects of stochastic variation in the environment due to varying climatic conditions. Large annual variation was found in reproductive success. However, body mass of individual chicks at the end and be ginning of the nestling period was strongly correlated in two of the study years, suggesting consistent variation among parents in their ability to feed offspring. Furthermore, chick mass was related both to overall body size and to body mass of their parents. Short brooding-shift intervals also were important for growth and survival of chicks. The probability of chick survival to the age of 30 days (ca. two weeks before fledging) was strongly correlated with chick mass when the chick was left unattended. However, the relative importance of different parental characteristics differed between years. These results show that reproductive success of the Antarctic Petrel is influenced by stochastic variation in the environment, probably re lated to climatic conditions. Effects of this stochastic variation may depend on body mass and/ or body condition of the parents.
Full-text: https://sora.unm.edu/sites/default/files/journals/auk/v114n03/p0333-p0340.pdf
Keywords: Dronning Maud Land; NARE 1989/90; NARE 1991/92; NARE 1992/93; fugler; ornitologi; petreller; zoologi

A stable isotope pilot study from blue ice areas at Jutulsessen, Dronning Maud Land, Antarctica - Thomsen, Henrik Højmark; Hagen, Jon Ove (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; innlandsis; isbre; klimaendringer

Regulation of foraging trips and costs of incubation shifts in the Antarctic petrel (Thalassoica antarctica) - Tveraa, Torkild; Lorensten, Svein-Håkon; Sæther, Bernt-Erik (Behavioral Ecology, 1997)
In species where incubation is shared by both parents, the mate's ability to fast on the nest may constrain the time available for foraging. The decision to return to the nest should therefore be a compromise between an animal's own foraging success and its mate's ability to fast on the nest. To examine how the body conditions of incubating Antarctic petrels, Thalassoica antarctica, influence both the length of foraging trips and incubation shifts, we experimentally handicapped females by increasing their flight costs during a foraging trip by adding lead weights to their legs. Handicapped females spent more time at sea and had lower body conditions at arrival to the colony than controls, and, moreover, females in poor body condition at arrival to the colony spent generally more time at sea than those with higher body condition. The prolonged time period spent at sea by handicapped females was associated with higher desertion rates than among controls. The time the incubating mates fasted increased with their body condition at arrival to the colony, suggesting that a high body condition of the incubating bird may reduce the probability of nest desertion. Accordingly, our results suggest that the time spent foraging is adjusted to the body conditions of both the foraging and incubating mate.
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Seabird research at Svarthamaren during NARE 1996-1997 - Tveraa, Torkild; Røv, Nils; Aanes, Ronny; Jensen, Henrik (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller

Spectral reflectance of snow and glacier ice as measured in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; glasiologi; isbre

Epica Dronning Maud Land pre site survey 1996/97 - Winther, Jan-Gunnar; Broeke van den, Michiel R.; Conrads, Louk; Eiken, Trond; Hurlen, Robert; Johnsrud, Georg; Karlöf, Lars; Onarheim, Stig; Richardson, Cecilia; Schorno, Raymond (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; akkumulasjon; innlandsis; is radar; meteorologi; snø radar; topografi

Studies and monitoring of climate-sensitive melt areas in Jutulgryta - Winther, Jan-Gunnar; Liston, Glen E; Bruland, Oddbjørn; Elvehøy, Hallgeir; Sand, Knut (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; hydrologi; klima; meteorologi

Ahlmannryggen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Pages: Blad/Sheet G5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Pages: Blad/Sheet G6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Effects of Egg Size and Parental Quality on Early Nestling Growth: An Experiment with the Antarctic Petrel - Amundsen, Trond; Lorentsen, Svein-Hakon; Tveraa, Torkild (Journal of Animal Ecology, 1996)
A large number of studies have reported a positive relationship between the egg size of birds and the subsequent growth and/or survival of nestlings, but such effects may partly be due to confounding variables, e.g. parental quality. In order to evaluate the potential effects of egg size, and of parental quality, on early nestling growth in the Antarctic petrel, we performed an experiment in which eggs of different size were swapped between nests. 2. From a sample of 300 nests with eggs of known size, we selected eggs belonging to the lower quartile (small eggs), and those belonging to the upper quartile (large eggs), with respect to volume. Half of the small eggs were exchanged with small eggs from other nests, and the other half with large eggs. A similar procedure was used for large eggs. Growth and survival of the nestlings were recorded until 12 days old. 3. Hatching success was positively related to egg size. 4. Egg size influenced nestling body mass until the age of 3 days, and tarsus length was affected until 12 days old. However, these effects were not due to an effect of egg size on growth rates, but reflected instead the influence of egg size on hatchling size. 5. In contrast to most previous studies, we found no effect of parental quality (as reflected in the size of own eggs) on foster nestling size or growth until 12 days old. This could be because egg size does not reliably reflect parental quality in the species, or because parental effects become evident only at later nestling stages. 6. We discuss why egg size variation is maintained in this and other species where egg size influences parental fitness through the survival of eggs or nestlings.
Publisher: [Wiley, British Ecological Society]
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Geodetic measurements at Vestfjella and Heimefrontfjella - Barstad, Bjørn; Luktvasslimo, Brit Åse (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; ekspedisjoner; geodesi; satellittbilder; topografi

A century of accumulation and temperature changes in Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn; Gundestrup, Niels; Mayewski, Paul; Whitlow, Sallie; Twickler, Mark (Journal of Geophysical Research: Atmospheres, 1996)
Keywords: Dronning Maud Land; akkumulasjon; klima; målinger; snø; temperatur

Regulation of Food Provisioning in the Antarctic Petrel Thalassoica antarctica - Lorentsen, Svein-Håkon (Journal of Animal Ecology, 1996)
1. Life-history theory predicts that individual birds should invest in reproduction according to their current body condition and the future prospects for survival and reproduction. Thus, it could be expected that current adult body condition should significantly influence food provisioning rates, food loads and concurrent chick growth in the Antarctic petrel. 2. In order to study the significance of parental body condition I correlated meal sizes, feeding frequencies and chick growth with the body condition of the parents. 3. There was a strong correlation between the average meal size delivered to a chick and its growth rate. Adult body condition at the time of hatching was strongly correlated with the average size of meals delivered to individual chicks. Male and female body condition at the time of hatching and average body condition of the pair at the first incubation shift and at hatching significantly influenced the body mass of the chick on day 30. Male body condition and the average body condition of the pair correlated significantly with the growth rate of the chick. 4. The difference in body mass at the age of 30 days of chicks from parents with good body condition compared with chicks from parents with poorer body condition was nearly double that expected. 5. The results strongly suggest that the effort spent during the chick-rearing period, and thus reproductive success, is regulated by the body condition of the parents.
Publisher: [Wiley, British Ecological Society]
Keywords: Dronning Maud Land; NARE 1991/92; fugler; ornitologi; petreller; zoologi

Seabird research at Svarthamaren during NARE 1993/94 - Lorentsen, Svein-Håkon; Amundsen, Trond; Røv, Nils; Tveraa, Torkild (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; fugler; ornitologi

Mass balance and dynamics on Jutulstraumen ice stream during NARE 1993/94 - Melvold, Kjetil; Hagen, Jon Ove; Laumann, Tron; Tonning, Tore (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi; isstrøm

Anhydrobiosis and cold tolerance in tardigrades - Sømme, Lauritz (European Journal of Entomology, 1996)
A review of the literature regarding anhydrobiosis and cold tolerance in tardigrades is presented. During increasing desiccation, invertebrates like tardigrades, rotifers, nematodes and some collembolans are able to shut down metabolism to undetectable levels. When tardigrades are entering anhydrobiosis, a tun-like structure is formed, facilitated by structural adaptations of the cuticle. Slow dehydration is essential for tun formation, and the accumulation of trehalose during this process may help to stabilize phospholipids and proteins. Wax extrusion on the cuticle surface reduces transpiration. A fraction of 5-15% of the initial body water is retained during anhydrobiosis. Tardigrades are principally aquatic organisms, but anhydrobiosis makes it possible for some species to live in habitats with changing moisture conditions. Tardigrades in anhydrobiosis may tolerate exposure to freezing temperatures of liquid gases, and some species also survive such temperatures in their hydrated state. Few investigations are available on the relation of tardigrades to temperatures more representative to their natural environments. Experimental studies, however, from Greenland and the Antarctic Continent suggest that some species overwinter both in a hydrated frozen state and in anhydrobiosis. During the summer, a number of tardigrade species have been recorded from cryoconite holes, formed on the surface of glaciers. These species are freeze tolerant since their habitats are permanently frozen during the winter.
Keywords: Antarktis; Dronning Maud Land; biomonitorering; bjørnedyr; entomologi; kuldetoleranse; polarområdene; virvelløse dyr

Glaciological measurements at Jutulgryta - Winther, Jan-Gunnar; Sand, Knut; Elvehøy, Hallgeir; Bøggild, Carl Egede (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi

Egg Size and Early Nestling Growth in the Snow Petrel - Amundsen, Trond (The Condor, 1995)
I studied egg size variation, and the influence of egg size on early nestling growth, in Snow Petrels Pagodroma nivea breeding at Svarthamaren, Dronning Maud Land, Antarctica (71 degrees 53'S, 5 degrees 10'E). Egg sizes ranged from 36.4 to 52.1 cm(3), with a mean of 44.9 cm(3). Hatching occurred during 16-24 January, with a median hatching date of 20 January. Egg size had a significant effect on the body mass of hatchlings, explaining 30% of the variation in body mass of nestlings hatched within the last 24 hr, and 58% of the body mass variation of nestlings weighed while still slightly wet. An experiment, which included swapping of eggs between nests, together with analyses of non-manipulated nests, revealed an effect of egg size on nestling body masses at ages of two and four days. From the experiment, no effect of maternal quality as expressed by her egg size could be found. At an age of four days, 40% of the nestlings were left alone in the nest by their parents. Nestlings not attended by a parent at this age were significantly lighter than were those with parental company. Parents that had left their young by the time these were four days old may have been poor quality birds, as indicated by the tendency for such birds to have laid smaller eggs than had those still tending their young at the same nestling age.
Publisher: American Ornithological Society
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Regulation of parental investment in the Antarctic petrel Thalassoica antarctica: an exchange experiment - Andersen, Reidar; Sæther, Bernt-Erik; Pedersen, Hans Christian (Polar Biology, 1995)
An experiment was conducted on the Antarctic petrel to test whether the parents were able to respond to changes in food demand of their offspring. Two experimental groups were formed by replacing eight 20-day-old chicks with 10-day-old chicks, and vice versa. The growth rate of chicks in the experimental groups was compared with that in two control groups with chicks of known age. The growth rate of 10-day-old chicks in the nests of parents which initially had 20-day-old chicks did not differ significantly from that in their respective control groups. This indicates that those parents were able to raise a new young nestling, despite having already raised another chick from hatching to 20 days. However, the 20-day-old chicks placed in nests with 10-day-old chicks had a significantly lower growth rate than their control group. Feeding rate per day and nest did not differ significantly among any of the groups. This suggests that the observed difference in growth rate between 20-day-old chicks is related to a lower amount of food delivered per visit to experimental chicks. Thus, in the Antarctic petrel, the feeding rate apparently is not regulated by the status of the chick, but by the parents' ability to gather food or willingness to provide food for the chicks.
Keywords: Dronning Maud Land; NARE 1989/90; fugler; ornitologi; petreller; zoologi

Incubation and brooding performance of the Antarctic Petrel Thalassoica antarctica at Svarthamaren, Dronning Maud Land - Lorentsen, Svein-Håkon; Røv, Nils (Ibis, 1995)
Antarctic Petrel Thalassoica antarctica incubation and brooding effort was studied at Svarthamaren, Dronning Maud Land, during the austral summer of 1991-1992. The females probably left the nest site shortly after egg laying. The duration of incubation and brooding shifts as well as the daily weight loss (absolute and proportionate) were comparable with those of other similar-sized procellariform species. Males spent more time incubating and brooding than did females, suggesting higher female energy stress due to egg laying, Incubating birds which were below average weight were likely to desert the nests before their mates returned from feeding trips. Both males and females lost approximately one-fifth of their body-weight during their first incubation shifts. Nevertheless, they increased their initial weights from egg laying to hatching and had their highest initial weights when they returned to start the shift during which the egg hatched. No factors related to adult body-weight explained the duration of the incubation shifts, Both males and females gained weight at a higher rate when at sea than they lost it during incubation, and it is suggested that factors unrelated to food availability or individual feeding skills may be important in regulating the duration of the incubation shifts and the stay at sea.
Keywords: Dronning Maud Land; NARE 1991/92; fugler; ornitologi; petreller; zoologi

Distribution and diving behaviour of crabeater seals (Lobodon carcinophagus) off Queen Maud Land - Nordøy, Erling S.; Folkow, Lars; Blix, Arnoldus Schytte (Polar Biology, 1995)
Eight crabeater seals (Lobodon carcinophagus) (three females, five males), ranging in body mass between 125 and 220 kg, were captured off Queen Maud Land (70-72 degrees S, 7-16 degrees W) during the last week of February, just after moulting, and tagged with Argos satellite-linked dive recorders to provide data on location and diving depth and duration. During the first few weeks of March the seals were moving in the pack ice along the continental shelf edge, close to the coast of Queen Maud Land. In April and May, when the pack ice extended northwards, most of the seals moved north, one reaching 63 degrees S in late May. In the first half of June the two remaining seals turned south and moved back deep into the pack ice. The seals made about 150 dives per day each throughout the study period. Ninety percent of these were made to depths of less than 52 m. Individual maximum diving depths varied between 288 and 528 m. In March the seals were most active at night, when the dive depth was shallower than during the day. In April and May the seals were more active during day-time, with an absence of any diurnal change in diving depth. These results support the notion that crabeater seals predominantly feed on krill in Antarctic pack ice, even when winter returns to the waters off Queen Maud Land.
Keywords: Dronning Maud Land; Sørishavet; Weddellhavet; biodiversitet; marin biologi; seler; telemetri; zoologi; økologi

Cold tolerance in Tardigrada from Dronning Maud Land, Antarctica - Sømme, Lauritz; Meier, Terje (Polar Biology, 1995)
Survival at low temperatures was studied in three species of Tardigrada from Muhlig-Hofmannfjella, Dronning Maud Land, Antarctica. Both hydrated and dehydrated specimens of Echiniscus jenningsi, Macrobiotus furciger and Diphascon chilenense had high survival rates following exposure to -22 degrees C for ca. 600 days, and dehydrated specimens following 3040 days at this temperature. In hydrated E. jenningsi, mortality increased with the duration of exposure from 7 to 150 days at -80 degrees C, while mortalities of the two other species did not change. Hydrated specimens of all species were rapidly killed at -180 degrees C, but all species exhibited good survivorship in the dehydrated state after 14 days at -180 degrees C. In conclusion, hydrated tardigrades are able to survive extended periods at low temperatures, and dehydrated specimens are even better adapted to survive overwintering on Antarctic nunataks.
Keywords: Dronning Maud Land; biologi; biomonitorering; bjørnedyr; kuldetoleranse; virvelløse dyr

Spatial and temporal patterns in snow accumulation, western Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn (Journal of Glaciology, 1994)
During the Swedish Antarctic Expedition to Dronning Maud Land, Antarctica, 1988–89 the net accumulation was estimated for an area from the coast to about 400 km inland. Stake measurements were used to obtain the spatial variability and firn cores were used for the temporal variability. The mean annual accumulation for the period 1976–88 is about 0.4mw.e. for Riiser-Larsenisen and about 0.3mw.e. for the area above the grounding line. The accumulation rate at higher altitudes, > 2500 m a.s.1., is about 0.1 m w.e. for 1955–88. One record from the ice shelf covers the period 1957–88, and suggests an increase in accumulation of about 12%. Between 1976 and 1988, the accumulation has decreased by about 50%, most likely due to lower temperatures as suggested by the temperature record from Halley.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi

Sex determination of Antarctic Petrels Thalassoica antarctica by discriminant analysis of morphometric characters - Lorentsen, Svein-Håkon; Røv, Nils (Polar Biology, 1994)
We present data on sexual dimorphism in some morphological measurements (wing length, head length, bill depth and bill length) in the Antarctic Petrel Thalassoica antarctica. Males were on average larger than females for all measurements. Sexual dimorphism was on average largest for bill depths whereas wing lengths discriminated least between the sexes. A discriminant function including bill depth, head length and wing length correctly sexed 92% of the sample. Due to between-measurer variation it is recommended that morphometric measurements obtained by others on sexed birds are compared with ours before proceeding with the use of the discriminant function on unsexed individuals.
Keywords: Dronning Maud Land; NARE 1991/92; biodiversitet; fugler; ornitologi; zoologi; økologi

Oceanographic and glaciologic investigations through Jutulgryta, Fimbulisen in the 1991/92 season - Østerhus, Svein; Orheim, Olav (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Dronning Maud Land; NARE 1991/92; glasiologi; oseanografi

Seabird studies at Svarthamaren, Dronning Maud Land - Røv, Nils; Lorentsen, Svein-Håkon; Bangjord, Georg (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Dronning Maud Land; NARE 1991/92; fugler; ornitologi

Dronning Maud Land - Tollefsen, Ivar (Mortensen, 1994)
Keywords: Dronning Maud Land; Sydpolen; ekspedisjoner; fjellklatring; polarekspedisjoner

Spectral bi-directional reflectance of snow and glacier ice measured in Dronning Maud Land, Antarctica - Winther, Jan-Gunnar (Annals of Glaciology, 1994)
Visible and near-infrared spectral reflectances of snow and superimposed ice were measured in Dronning Maud Land, Antarctica, during the 1992-93 austral summer. Spectral-reflectance curves of both snow and superimposed ice remain high ( > 80%) in the visible region. A pronounced decrease in reflectance appears in the near-infrared, especially for superimposed ice. Superimposed ice with a 1 cm thick surface layer of ice-bound snow crystals had a considerably higher reflectance than superimposed ice containing only a few snow crystals. Furthermore, these data prove that snow and superimposed ice reflect solar radiation specularly and suggest that the anisotropy strengthens with increasing wavelengths. Integrated in-situ reflectances corresponding to Landsat TM bands 1-4 show that TM band 1 is least affected, whereas TM band 4 is most affected by anisotropy. Furthermore, the anisotropy increases with increasing off-nadir viewing angles up to an angle corresponding to 90°-θs (θs = solar elevation). For a 15° off-nadir sensor-observation angle, the average snow reflectance for TM bands 1–4 is about 10% higher than at nadir. Similarly, the apparent reflectance can be more than 50% higher than the nadir reflectance for larger observation angles. Consequently, if satellite-derived reflectances are going to be considered as absolute values, a topographic-correction model is needed to correct for the effects of anisotropy.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi

Granulites and garnet–cordierite gneisses from Dronning Maud Land, Antarctica - Bucher-Nurminen, Kurt; Ohta, Yoshihide (Journal of Metamorphic Geology, 1993)
The central sector of Mühlig-Hofmannfjellet (3°E/71°S) in western Dronning Maud Land (East Antarctic shield) is dominated by large intrusive bodies of predominantly orthopyroxene-bearing quartz syenites (charnockites). Metasedimentary rocks are rare; however, two distinct areas with banded gneiss–marble–quartzite sequences of sedimentary origin were found during the Norwegian Antarctic Research Expedition NARE 1989/90. Cordierite-bearing metapelitic gneisses from two different localities contain the characteristic mineral assemblage: cordierite + garnet + biotite + K-feldspar + plagioclase + quartz ± sillimanite ± spinel. Thermobarometry indicates equilibration conditions of about 650°C and 4 kbar. Associated orthopyroxene–garnet granulites, on the other hand, revealed pressures of about 8 kbar and temperatures of 750°C. The earlier granulite facies metamorphism is not well preserved in the cordierite gneisses as a result of excess K-feldspar combined with interaction with an H2O-rich fluid phase, probably released by the cooling intrusives. These two features allowed the original high-grade K-feldspar + garnet assemblages to recrystallize as cordierite–biotite–sillimanite gneisses, completely re-equilibrating them. Phase relationships indicate that the younger metamorphic event occurred in the presence of a fluid phase that varied in composition between the lithologies.
Keywords: Dronning Maud Land; NARE 1989/90; geokjemi; geologi

Nature environment map: Gjelsvikfjella and Western Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica - Høgvard, K (Norsk Polarinstitutt, 1993)
Pages: Blad/Sheet 1 Publication Title: Norsk Polarinstitutt Temakart Nr. 24 Place: Oslo
Keywords: Dronning Maud Land; NARE 1984/85; NARE 1989/90; geografi; kartlegging

Notes on the ecology and physiology of the Antarctic oribatid mite Maudheimia wilsoni - Sømme, Lauritz; Strømme, Alexander; Zachariassen, Karl Erik (Polar Research, 1993)
The oribatid mite Maudheimia wilsoni Dalenius was found to be numerous on the underside of stones at Jutulsessen (72-degrees-S, 3-degrees-E) in Dronning Maud Land, Antarctica. Daily temperature fluctuations of the microhabitat from as high as 19-degrees-C and to as low as -17-degrees-C were observed during the austral summer. Optimal activity of the mites occurred at 10-degrees-C. Even in January the mean supercooling point of adult mites was as low as - 30.8 +/- 4.7-degrees-C. Haemolymph osmolality ranged from 500 to 800 mOsmol and thermal hystersis freezing points from -4.7 to - 6.1-degrees-C. Adult mites had a mean water content of 43.6% and a water loss rate of 0.12 mug h-1 at 15-degrees-C and 10% relative humidity.
Keywords: Dronning Maud Land; NARE 1989/90; entomologi; midder; miter; virvelløse dyr; zoologi; økofysiologi; økologi

Jutulsessen: Fimbulheimen (Norsk Polarinstitutt, 1992)
Place: Oslo
Keywords: Dronning Maud Land; Troll forskningsstasjon; geografi; kartlegging; satellite bilder

H.U. Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad H6S Place: [Oslo]
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad/Sheet H5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad/Sheet J5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1991)
Pages: Blad/Sheet J6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Thermoregulatory abilities in chicks of the Antarctic Petrel (Thalassoica antarctica) - Bech, Claus; Mehlum, Fridtjof; Haftorn, Svein (Polar Biology, 1991)
We studied the thermoregulatory capacity of Antarctic Petrel chicks, Thalassoica antarctica, breeding in a large colony in Queen Maud Land (71-degrees-53'S, 5-degrees-10'E) on the Antarctic continent. Compared to newly hatched chicks of other birds, those of the Antarctic Petrel are characterized by a relatively high standard metabolic rate (SMR) and thermal conductance. Their metabolic scope is limited, however, being only 1.6 times the SMR, and they consequently depend on parental brooding to maintain T(b). At an age of 11 days the chicks become thermally independent and are left alone in the nest. The chicks keep a relatively high body temperature (> 36-degrees-C) throughout their early development and we found no indication that they normally experience hypothermia. A significant positive relationship between latitude of breeding and SMR of the hatchlings is shown to exist for procellariiform birds. It is suggested that the high SMR found in Antarctic Petrel hatchlings could be a prerequisite for achieving a high growth rate, rather than being of any thermoregulatory significance.
Keywords: Dronning Maud Land; NARE 1984/85; fugler; ornitologi; petreller; zoologi

Humoral-immunologiske endringar ved korttidsisolasjon i Antarktis - Molvær, Otto Inge; Matre, Roald; Bendiksen, Fredrik S; Reitehaug, Per-Ivar; Hjelle, John O (NUTEC, 1991)
https://urn.nb.no/URN:NBN:no-nb_digibok_2011012708090
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; immunologi; mikrobiologi

Antarktispetrellen: på grensen av det mulige - Sæther, Bernt-Erik (Naturen, 1991)
Keywords: Dronning Maud Land; fugler; ornitologi

Geological observations in Gjelsvikfjella and Mühling-Hofmannfjella - Bucher-Nurminen, Kurt; Ohta, Yoshihide; Austrheim, Håkon; Dallmann, Winfried K (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geologi

Geology around the Norwegian Antarctic station "Troll", Jutulsessen, Dronning Maud Land - Dallmann, Winfried K; Austrheim, Håkon; Bucher-Nurminen, Kurt; Ohta, Yoshihide (Norsk Polarinstitutt, 1990)
During the Norwegian Antarctic Research Expedition 1989/90, a pennanent, unmanned research station was raised in Jutulsessen, Gjelsvikfjella, western Dronning Maud Land. The present report is a description of the geology of the area accessable from the station. Exposures of rocks in this part of Dronning Maud Land are restricted to a coastal mountain chain at c. 200-250 km distance from the ice shelf edge at elevations between 1000 and 3000 m. Quaternary deposits are particularly restricted to the inner parts of the Jutulsessen glaeier cirques. Deposits are till and talus which locally are admixing at slope angles of c. 25°. Moraines are poorly developed. Patterned ground ('stone pits') are common at slope angles below c. 15°. Recently active phenomena of special interest are ice-margin meltwater lakes with pingo-like 'blisters " the deep frost-shattering all over the mountain walls and hoIes in rock surfaces as a result of wind activity with grinding particles. The bedrock belongs to the East Antarctic craton. The area under consideration (western Miihlig-Hofmannfjella and Gjelsvikfjella) consists of high-grade metamorphic rocks and fonns one of the world's best exposed granulite terranes. Orthogneisses and minor metasediments have been intruded by a series of charnockites, partly altered to granulites (the 'Svarthamaren charnockite complex'), and a sequence of dyke rocks. Migmatization has affected large parts of the gneisses. Both gneisses and granulites/charnockites show abundant evidence of transition from granulite to amphibolite facies and vice versa, and the important role of fluid-rock interactions leading to these processes can be studied. The gneisses at Jutulsessen show a complex defonnation history. They are thought to be derived from granitic intrusions, though minor amounts of high-grade metamorphic, metapelitic gneisses may represent their original host rocks. Early tectonism (c. 1000-1200 m.y.) produced gneissosity, compositional banding and a leucosome phase under high-grade metamorphic conditions. This was followed by multiple and complex intrusive activity, partial migmatization and a tectonic overprint with abundant shear defonnation under amphibolite-facies conditions (c. 450-500 m.y.).
Publication Title: Meddelelser
Keywords: Dronning Maud Land; NARE 1989/90; berggrunnsgeologi; geologi

Geodetic measurements in Dronning Maud Land - Eiken, Trond; Luktvasslimo, Brit Åse; Lytskjold, Bjørn (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geodesi

I hjertet av Antarktis; Norge i Antarktis - Imbert, Bertrand C; Hem, Arne (Polarforskningens pionerer, 1990)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; hvalfangst; oppdagelsesreiser

Radio-echo investigations in Dronning Maud Land - Kennett, Michael (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geofysikk; isshelf; isstrøm; klimaendringer

Medical contingency and biomedical research - Molvær, Otto Inge; Bendiksen, Fredrik S; Reitehaug, Per-Ivar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; biomedisin; medisin

Report of the Norwegian Antarctic Research Expedition 1989/90 - Norsk, Polarinstitutt (Norsk Polarinstitutt, 1990)
Publication Title: Meddelelser
Keywords: Antarktis; Dronning Maud Land; NARE 1989/90; Troll forskningsstasjon; Weddellhavet; geologi; marin økologi; meteorologi; zoologi

Geology of Gjelsvikfjella and western Mühlig-Hofmannfjella, Dronning Maud Land, east Antarctica - Ohta, Yoshihide; Tørudbakken, Bjørn; Shiraishi, Kazuyuki (Polar Research, 1990)
As a part of the Norwegian Antarctic Research Expedition 1984/85, geological mapping was performed in Gjelsvikfjella and western Muhlig-Hofmannfjella, Dronning Maud Land. The northern part of Gjelsvikfjella is dominated by the Jutulsessen metasupracrustals which have been intruded by a major gabbroic body and several generations of dykes. To the south the metasupracrustals gradually transform into the Risemedet migmatites. In western Muhlig-Hofmannfjella the bedrock is dominated by the large Svarthamaren Charnockite batholith. The batholith is bordered by the Snotoa metamorphic complex outcropping to the south and west in Muhlig-Hofmannfjella and it is characterized by a high content of partly assimilated country rock inclusions. Mineral paragenesis and geothermometry/geobarometry suggest a two-stage tectonothermal-igneous history with an initial intermediate pressure, upper amphibolite to granulite facies metamorphism followed by high temperature transformations related to the charnockite intrusion. The age of the initial tectonothermal event is probably about 1,100 Ma. Geochronological work in the present study (Rb/Sr whole rock) gave an age of 500 +/- 24 Ma for the Svarthamaren Charnockite, interpreted to record the age of crystallization. Late brittle faulting and undeformed dolerite dykes outcropping in Jutulsessen are believed to be related to Mesozoic crustal stretching in the Jutulstraumen-Pencksokket Rift Zone to the west.
Keywords: Dronning Maud Land; NARE 1984/85; geologi

Studies on, and underneath, the Ice Shelf Fimbulisen - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; isshelf

Aspects of reproductive behaviour in a population of South Polar skua Catharacta maccormicki in Dronning Maud Land - Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Studies of breeding biology of Antarctic petrel and snow petrel in Mühlig-Hofmannfjella, Dronning Maud Land - Røv, Nils (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Ecophysiological adaptations in mites and collembolans in Dronning Maud Land - Strømme, Alexander (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; midder; miter; virvelløse dyr; zoologi; økofysiologi

Studies on the factors determining variation in the reproductive success of the Antarctic petrel Thalassoica antarctica in Svarthamaren, Mühlig-Hofmannfjella - Sæther, Bernt-Erik; Andersen, Reidar; Pedersen, Hans Christian (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; fugler; ornitologi; reproduksjon; zoologi

Glaciological and meteorological measurements in Dronning Maud Land - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; meteorologi